2014
DOI: 10.1016/j.neo.2014.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to the mTOR Inhibitor Temsirolimus Alters Adhesion and Migration Behavior of Renal Cell Carcinoma Cells through an Integrin α5– and Integrin β3–Dependent Mechanism

Abstract: Inhibitors of the mammalian target of rapamycin (mTOR) have improved the treatment of renal cell carcinoma (RCC). However, chronic drug exposure may trigger resistance, limiting the utility of these agents. The metastatic behavior of RCC cells, susceptible (RCC(par)) or resistant (RCC(res)) to the mTOR inhibitor temsirolimus, was investigated. Adhesion to vascular endothelium or immobilized collagen and fibronectin was quantified. Chemotactic motility was evaluated with a modified Boyden chamber assay. Integri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Chronic treatment of prostate cancer cells with another mTOR inhibitor, everolimus, has also been associated with increased metastatic activity [ 20 ]. The same increase in metastatic activity has been observed in renal cell carcinoma cells with acquired resistance towards TEM [ 21 ]. It is not yet clear whether mTOR represents the pivotal element triggering invasion.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Chronic treatment of prostate cancer cells with another mTOR inhibitor, everolimus, has also been associated with increased metastatic activity [ 20 ]. The same increase in metastatic activity has been observed in renal cell carcinoma cells with acquired resistance towards TEM [ 21 ]. It is not yet clear whether mTOR represents the pivotal element triggering invasion.…”
Section: Discussionsupporting
confidence: 67%
“…Integrin α5 was not only down-regulated in PC3 res cells but was also found to be reduced in TEM-resistant renal cell carcinoma cells [ 21 ] or in prostate cancer cells with acquired resistance to everolimus [ 20 ]. This might reflect a generalized response to chronic mTOR-blockade, although the relevance of this behavior is not totally clear.…”
Section: Discussionmentioning
confidence: 99%
“…Whether due to an acquired or intrinsic resistance or due to the development of undesired feedback loops remains unclear, but this does indicate that not all bladder cancer patients may profit equally well from amygdalin. In line with this speculation, it has recently been shown that resistance development is accompanied by a functional switch of integrin receptors, driving tumor cells to high motility [12] .…”
Section: Discussionmentioning
confidence: 74%
“…Earlier investigations have shown that everolimus-resistance drives RCC cells towards high proliferation and motility [11, 12]. SFN not only reduced growth of everolimus-sensitive tumor cells but also counteracted aggressive proliferative and invasive activity of everolimus-resistant RCC cell lines.…”
Section: Discussionmentioning
confidence: 98%